Enhanced ferromagnetism in edge enriched holey/lacey reduced graphene oxide nanoribbons. (15th October 2017) - Sahu, Vikrant; Maurya, V.K.; Singh, Gurmeet; Patnaik, S.; Sharma, Raj Kishore
Abstract: Incorporation of magnetism in graphene based compounds holds great promise for potential spintronic applications. By optimizing point defects and high edge density of defects, we report many-fold increase in the ferromagnetic saturation moment in lacey/holey reduced graphene oxide nanoribbons (LRGONR) as compared to other graphene derivatives. The samples were synthesized using chemical unzipping methodology. Detailed structural and morphological characterizations are discussed that include XRD, Raman, SEM, HRTEM and XPS measurements. Brilluoin function analysis to magnetization data reflects best fit for J = 7/2 with a saturation moment of 1.1 emu/g. The microscopic origin of magnetization in LRGONR is assigned to high edge defect density which has also been correlated to microstructure. Graphical abstract: Highlights: Defect induced ferromagnetism in graphene nanoribbon. Graphene edges upon unzipping MWCNT increased magnetism to many fold. Brilluoin function analysis reflects J = 7/2 with a saturation moment of 1.1 emu/g.